Функції як складник компетенції Міністерства розвитку економіки, торгівлі та сільського господарства україни у сфері забезпечення економічної безпеки держави - Кошиков, Д. О.; Koshykov, D. O. (Науковий вісник публічного та приватного права. - 2019. - Вип. 5, т. 2. - С. 124-129, 2019)
З’ясовано зміст та складові елементи поняття «компетенція», визначено компетенцію центральних органів виконавчої влади в межах реалізації державної політики у сфері забезпечення економічної безпеки держави. Встановлено та охарактеризовано окремі структурні елементи компетенції Міністерства розвитку економіки, торгівлі та сільського господарства України у сфері забезпечення економічної безпеки держави, такі як предмет відання, який обмежується сферою національної економічної безпеки; повноваження; функції (нормативна, методична, аналітична, організаційна, координаційна, мобілізаційна, охоронна, а також функції планування, прогнозування, регулювання, моніторингу).

It is emphasized that the higher bodies of state power are endowed with broad powers in specific spheres of rulemaking (Verkhovna Rada of Ukraine), law enforcement (Cabinet of Ministers of Ukraine), law enforcement (courts, prosecutor’s offices, Antimonopoly Committee of Ukraine). In this regard, it is substantiated that the central executive bodies, in particular the Ministry of Development of Economy, Trade and Agriculture of Ukraine, unlike the higher bodies of state power, are vested with complex competence that is, they have powers both in the areas of rulemaking, enforcement and in law enforcement direction. Having clarified the content and constituent elements of the concept of “competence”, the competence of the central executive authorities within the implementation of state policy in the sphere of ensuring the economic security of the state to which the Ministry of Economic Development, Trade and Agriculture of Ukraine should be referred is determined. The tasks of the Ministry of Economic Development, Trade and Agriculture of Ukraine, as a structural element of its competence in the sphere of ensuring the economic security of the state, are proposed to ensure the formation and implementation of: the state price policy; state industrial policy; entrepreneurship; public procurement; innovation policy; Agriculture; agricultural production; intellectual property; trade and domestic services; industrial safety; management of objects of state property, corporate rights of the state; state investments of the state material reserve. The author establishes and characterizes certain structural elements of the competence of the Ministry of Economic Development, Trade and Agriculture of Ukraine in the sphere of ensuring the economic security of the state: subject matter, which is limited to the sphere of national economic security; powers; powers; functions (regulatory, methodological, analytical, organizational, coordination, mobilization, security, as well as functions of planning, forecasting, regulation, monitoring).

Выяснено содержание и составные элементы понятия «компетенция», определена компетенция центральных органов исполнительной власти в рамках реализации государственной политики в сфере обеспечения экономической безопасности государства. Установлены и охарактеризованы отдельные структурные элементы компетенции Министерства развития экономики, торговли и сельского хозяйства Украины в сфере обеспечения экономической безопасности государства, такие как предмет ведения, ограничивающий сферу национальной экономической безопасности; полномочия; функции (нормативная, методическая, аналитическая, организационная, координационная, мобилизационная, охранная, а также функции планирования, прогнозирования, регулирования, мониторинга).
Кошиков, Д. О. Функції як складник компетенції Міністерства розвитку економіки, торгівлі та сільського господарства україни у сфері забезпечення економічної безпеки держави / Кошиков Д. О. // Науковий вісник публічного та приватного права. - 2019. - Вип. 5, т. 2. - С. 124-129. - DOI: https://doi.org/10.32844/2618-1258.2019.5-2.23.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; центральні органи виконавчої влади; central bodies of executive power; центральные органы исполнительной власти; Міністерство розвитку економіки, торгівлі та сільського господарства України; Ministry of Economic Development, Trade and Agriculture of Ukraine; Министерство развития экономики, торговли и сельского хозяйства Украины; повноваження; powers; полномочия; компетенція; competence; компетенция; функції; functions; функции; економічна безпека держави; economic security of the state; экономическая безопасность государства